Enhancing WSN Lifespan Based on Efficient-Energy Management Approach for Cluster Head Selection in IoT Application - Mehra, B.; Datar, A. (Radioengineering Society, 2025)
Wireless sensor networks (WSNs) are one of the most important components in the connected world i.e. Internet of Things (IoT). WSN is a network of distributed sensor nodes that communicate wirelessly to transmit and receive real-time data. These sensor nodes play a crucial role in monitoring various environments, enabling smarter decision-making and improving efficiency across numerous applications. This paper presents an energy-efficient protocol based on low energy adaptive clustering hierarchy (LEACH) for improving the lifetime of WSN. The proposed method modifies the basic LEACH protocol and incorporates the factors of residual energy of the network, number of neighbor nodes, average energy of the network, and threshold distance between the nodes and base station. The proposed work compares the result with the existing methods and has shown the improvement in the network performance parameter metrics. The simulation results show an improvement in the network lifetime due to better energy management, thus increasing the number of data packet transfers.The proposed method has shown improvement by 13% over the first dead (FD) node of EEBC-LEACH, 5% improvement over half dead (HD) node of PEGASIS, and 3% improvement over all dead (AD) nodes of FBCR-LEACH.
Keywords: Internet of Things (IoT); Wireless Sensor Network (WSN); LEACH; Cluster Head (CH) selection; proximity; network energy